Inequality in the Income of the Population as a Determinant of the Country's Economic Growth - Kocurová, Tamara; Hampel, David (Mendelova univerzita v Brně, 2020)
In this article, there is explored the dependence of economic performance and economic growth on income inequality expressed by Gini coefficient and S80/S20 ratio. Analysis is based on data collected upon EU countries in years 2007, 2012 and 2017. Cluster analysis points out to heterogeneity of EU countries in observed characteristics and enables creation of three groups of countries: postsocialistic, southern and northern. Regression analysis, which takes into account groups of countries, was used to assess and illustrate the dependence. The results show that income inequality has a negative impact on the country's GDP per capita, and its impact on economic growth differs for particular groups of countries.
Keywords: Cluster analysis; Economic growth; EU countries; GDP; Gini coefficient; Income inequality; Regression analysis; S80/S20 ratio